Bantuan Teknis Perencanaan Renovasi Masjid Ali Wal Asri di Kota Bengkulu - Tiya Suryadi Putri; Dewi, Ayu Komalasari; Lestari, Suci; Faris, Moh. Faisal (Nemui Nyimah, 2025)
The community service program activity was carried out at Ali Wal Asri Mosque, located in the city of Bengkulu. One of the main issues identified at the mosque is the need for a more comfortable and spacious indoor prayer area than what currently exists. This condition highlights the necessity for building renovations to meet these spatial and functional needs.The objective of this community service activity is to provide technical support in the form of a renovation design proposal for Ali Wal Asri Mosque. The design focuses on expanding the indoor prayer area, emphasizing spatial harmony and user comfort, as well as the addition of openings such as windows and doors. The activity involved a planning process that included preliminary data collection and surveys, analysis and decision-making, and design development that resulted in conceptual and technical drawings as references for construction.The final output of this community service activity is a completed renovation design and a Detailed Engineering Design (DED), which can be used by the foundation as a guideline for the renovation process and for preparing a Bill of Quantities (BoQ) to support fundraising efforts for the mosque’s development.